Axological exploration in psychotherapy: Logotherapy - Salomón Paredes, Alejandro Khaled (2016)
The present article discusses the methodology of logotherapy regarding the approach to the axiological experience questioner described. The influence of Max Scheler and phenomenological theory of values also psychotherapeutic Viktor Frankl proposal, based on intentionality as personal reaching out towards the values and meaning is explored, as well. Special attention to the implementation of a phenomenological attitude in the therapeutic process is provided. It also reflects on the contributions of Fabry and Lukas among others regarding the axiological approach in franklean existential analysis. Also, psychotherapeutic moments and key questions that can help the process are described.